Avaliação do processo de digestão anaeróbia de resíduos alimentares em reatores batelada e semi-contínuo - Gueri, Matheus Vitor Diniz (2017)
The generation of food waste grows as the demand for food increases, that is, it is bound to the entire food production chain. This emphasize new techniques must be developed to assure the proper handling and treatment of this organic residue. Anaerobic digestion of food waste then arise as a promising alternative for the treatment of food waste that simultaneously promote the generation of clean and renewable energy. Therefore, the present research aimed to perform anaerobic digestion of food waste from a popular restaurant, verifying the potential for energetic utilization. BMP assays were performed in 250 mL reactors to verify the biodegradability of food residues, and in a prototype 408 L anaerobic reactor, adapted with agitation and temperature control, operating in a semi-continuous feed mode with the food waste. The variables of control (solids, pH, VFA, alkalinity, Volatile Acid:Alkalinity ratio and organic loading) were collected 3 times a week, over 51 days, totaling 21 samplings. Reductions of COD and SV were obtained in the percentages of 81.63% and 23.58% for the BMP assay and 82.34 and 90.22% for the semi-continuous experiment. It was possible to reach the specific methane production of 0.311 Nm3 CH4.kgVSr-1 for the BMP assay and 0,444 Nm3 CH4.kgVSr-1 in the semi-continuous experiment. The daily production of the semi-continuous reactor was obtained the average of 220 Lbiogas.d-1; while the volumetric production of biogas obtained an average of 0.540 L.Lr-1d-1. It was verified too that there was the stability of the semi-continuous reactor, with a mean Volatile Acid:Alkality ratio of 0.49.